Redefinition of τ-Distance in Metric Spaces. (20th April 2017) - Suzuki, Tomonari
Abstract : The concept of τ -distance was introduced in 2001; on the other hand, that of τ -function was introduced by Lin and Du. Strongly inspired by τ -function, we introduce a new concept, which is a very slight generalization of τ -distance and is more natural than τ -distance. So we could say that we redefine τ -distance in some sense.